Standar Pos Observasi Bulan Kementerian Agama & BMKG (Analisis Terhadap POB. Blang Tiron, Bukit Pole Kompleks Perumahan PT. Perta Arun gas Lhokseumawe) - Muhammad Fauzi; Ismail Ismail (Astroislamica: Journal of Islamic Astronomy, 2023)
The implementation of the Rukyat hilal sighting includes an important concern for Muslims. Among the supports for the successful implementation of hilal sightings is the existence of standard and ideal hilal sightings. Based on the author's observations and interviews with reckoning and rukyat staff at the Lhokseumawe Ministry of Religion, POB Blang Tiron Bukit Pole housing complex PT. Perta Arun Gas Lhokseumawe still has not succeeded in seeing the new moon, especially for the sighting of the new moon at the beginning of Ramadan and the beginning of Shawwal (Idul Fitri). So that the POB Bukit Pole Blang Tiron housing complex PT. Perta Arun Gas Lhokseumawe has never printed data on the sighting of the new moon to the Indonesian Ministry of Religion's Hisab Rukyat Agency (BHR). This research uses qualitative methods with the type of research used is field research through direct observation in the field and uses theories taken from the literature in the form of books, journals and others to strengthen research. While the data collection technique uses descriptive analysis method. The research location is located at the Blang Tiron Moon Observation Post, Bukit Pole, Housing Complex of PT. Perta Arun Gas Lhokseumawe. The research results in this study are (1). Natural conditions of the Blang Tiron Bukit Pole Observation Post, Housing Complex of PT. Perta Arun Gas Lhokseumawe apparently has not met the standards set by the Ministry of Religion and the Meteorology, Climatology and Geophysics Agency (BMKG). (2). The success rate of Rukyat Hilal sightings at the POB Blang Tiron Bukit Pole Housing Complex PT. Perta Arun Gas Lhokseumawe still does not meet the average sighting of the new hilal as data on the hilal study spanning four years for the month of Ramadan and Shawwal 1438-1441 H/2017-2020 M.